“EFEKTIVITAS PELAYANAN TRANSPORTASI PUBLIK (STUDI PELAYANAN P.T ASDP PELABUHAN BASTIONG TAHUN 2017)” - wance, marno (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2018)
The Effectiveness of Employee Service Effectiveness of PT ASDP Ferry Bastiong Ternate in 2017 is still inadequate. This is because there is still a lack of technical apparatus in field apparatus in providing an understanding of the effective model of accountable and prompt servants in responding to problems occurring at the port of PT ASDP Bastion Ternate . Therefore, innovation has been done by P.T ASDP Ferry Bastion in Ternate in striving for the achievement of service success on the aspect of public port governance. One of them establishes cooperation with several agencies and to address the passenger safety issues that continue to be experienced by other transport models at the crash point in the town ofTernate. To answer these problems it must be analyzed comprehensively to find facts that occur in the field. So the method used in this study is descriptive qualitative. This qualitative descriptive study serves to explain and read the model of effective service on the port of PT ASDP Bastiong. Data collection techniques used there are some of the observations, interviews, documentation and use of related materials. The approach used is primary and secondary data Primary data source is a source of data obtained directly from the respondent or object studied, while the secondary data source is the source of data obtained through written documents, archives and others at the agency or institution related to the research. In determining the results of research on the pattern of relationships that occur then the theory used is a model of effectiveness measurement using Open Systems Perspective approach presented by Richard M. Steers which is divided into indicators of organizational management, environmental characteristics, characteristics of workers and management practices.